Resepsi Laki-Laki Urban Jakarta terhadap Konsep Laki-Laki Gentroseksual di Majalah FHM - Kertanegara, Rizky; Wulantari, Raden Ayu (CommLine, 2015)
The label for “new man” that developed after the phenomenon of metrosexual in the 2000s has been obsolete todays due to the emergence of its new term “gentrosexual”. Gentrosexual derived from the word gentleman and metrosexual. Men todays believe that their self-actualization were not only seen from their appearance or treatment. Thus, the gentrosexual men genre revealed by realizing their roles to the gender issues, but that did not leave the traditional values such as behavior, marriage and loyalty. The research based on an article in a FHM UK magazine, which was also published in its Indonesian edition about the gentrosexual man genre that became a new phenomenon among urban men. FHM Indonesia believed that the gentrosexual character has been experienced by most urban men readers. This issue is interesting to study because of the conceptual shift of man associated with their role in society. Shifting this concept can be associated with the same or different cultures and values that they have so far. This study aims to understand how readers interpret gentrosexual characters in FHM Magazine Indonesia. This research is a qualitative descriptive using reception theory. Stuart Hall states that the reader is an active audience who has a preferred reading of media texts. Hall then mentions three readings performed by the code reader that is dominant, negotiation, and opposition. Convenience sampling was used to select a sample with the criteria that have been set. The primary data obtained by in-depth interviews were then analyzed with a coding technique. While the secondary data obtained by the study of documents and literature.